PENGARUH MANAJEMEN LABA, UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP RETURN SAHAM DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERASI - AKHMAD SIGIT ADIWIBOWO (Universitas Pamulang, 2018)
The purpose of this research to obtain empirical evidence effect Earning Management, Size and Leverage effect to Stock Return and Dividend Policy can moderating effect Earning Management, Size and Leverage to Stock Return. The Population in this study are all maufacturing companies listed on the Indonesian Stock Exchange (BEI) the periode 2010-2012. Sampling method performed with purposive sampling method, the number of samples is 162 samples of 56 manufacturing companies. Data analysis used simple regresion analysis and moderated regression analysis.The result show that: (1) Earning Management is not significantly effect on Stock Return. (2) Dividen Policy able to significantly moderate the effect of Earning Management on Stock Return. (3) Size is significantly effect on Stock Return. (4) Dividen Policy is not able to significantly moderate the effect of Size on Stock Return. (5) Leverage is significantly effect on Stock Return. (6) Dividen Policy able to significantly moderate the effect of Size on Stock Return.